Modelo de avaliação de desempenho para ecossistemas de inovação com base na capacidade de inovação dos atores - Silva, Deoclécio Junior Cardoso da (2023)
This research explores innovation ecosystems, confirming their importance due to the dynamics of cooperation, information exchange, and promotion of entrepreneurship and innovation. The research investigates how ecosystems can foster innovation capacity, a crucial competitive advantage in complex contexts. The central question is: How to evaluate the performance of innovation ecosystems based on the innovation capacity of the participants? The main objective is to propose a performance evaluation model for such ecosystems. Therefore, this thesis was structured into 4 articles, to reach the outlined objective. Using two systematic literature reviews, seven key actors were identified: Startups, SMEs, Incubators, Technology Parks, Universities, Industry and Government (Article 1 and 2). In the subsequent stage (Article 3), the process of validation and definition of weights was carried out, under the prerogatives of the Fuzzy Delphi and Fuzzy methods, counting in this phase on the evaluation of 125 experts, divided into 7 previously mapped actors, thus generating 227 valid indicators in relation to the model. In this way, the model (Article 4) could be proposed, which made it possible to achieve the outlined objective. Thus, they generated theoretical contributions, as they filled gaps already highlighted with regard to the performance assessment of innovation ecosystems, as well as bringing to the literature a practical model to be applied in different areas. Furthermore, with regard to practical implications, this research contributes by providing information that decision makers, whether public or private, can use to assess innovation capacity, thereby generating relevant results for strategic alignments to improve performance. performance on this topic.